1999
DOI: 10.1137/s0036144599352836
|View full text |Cite
|
Sign up to set email alerts
|

Centroidal Voronoi Tessellations: Applications and Algorithms

Abstract: Abstract.A centroidal Voronoi tessellation is a Voronoi tessellation whose generating points are the centroids (centers of mass) of the corresponding Voronoi regions. We give some applications of such tessellations to problems in image compression, quadrature, finite difference methods, distribution of resources, cellular biology, statistics, and the territorial behavior of animals. We discuss methods for computing these tessellations, provide some analyses concerning both the tessellations and the methods for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
1,451
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,875 publications
(1,494 citation statements)
references
References 50 publications
6
1,451
0
2
Order By: Relevance
“…Centroidal Voronoi tessellation (CVT) [7] has been well studied and successfully applied to isotropic meshing [8] and anisotropic meshing [9], mainly computed by Lloyd's method. Liu et al [22] showed that the CVT energy has C 2 continuity and proposed to use the L-BFGS method, a variant of the quasi-Newton method, that outperforms the Lloyd's method for CVT computation.…”
Section: Optimization-based Methodsmentioning
confidence: 99%
“…Centroidal Voronoi tessellation (CVT) [7] has been well studied and successfully applied to isotropic meshing [8] and anisotropic meshing [9], mainly computed by Lloyd's method. Liu et al [22] showed that the CVT energy has C 2 continuity and proposed to use the L-BFGS method, a variant of the quasi-Newton method, that outperforms the Lloyd's method for CVT computation.…”
Section: Optimization-based Methodsmentioning
confidence: 99%
“…More optimal configurations can be reached through the perturbation of the robot team. This may also help to break off saddle points and symmetry configurations which sometimes result from CVTs [4].…”
Section: Perturbation Use Casementioning
confidence: 99%
“…Deployment and sweeping motion for robotic coverage of areas and boundaries (e.g., barriers) have previously also been referred to as blanket, barrier and sweep coverage [2]. A particular type of blanket coverage is Voronoi coverage [3], which arranges the robots in a final configuration that forms a so-called Centroidal Voronoi Tessellation (CVT) [4].…”
Section: Introductionmentioning
confidence: 99%
“…La tassellatura Voronoi è producibile nel piano o anche nello spazio. La formulazione matematica completa dell'algoritmo di Voronoi può essere reperita ad esempio in [43]. Le celle di un reticolo così creato sono statisticamente rappresentative, nelle due o tre dimensioni, della struttura a grani di un materiale metallico policristallino.…”
Section: Generazione DI Microstrutture Statisticamente Equivalentiunclassified